Service Learning Project Reflection in ARO - Karimi, Pohanmal Firoz Uzbek (Integrated Journal for Research in Arts and Humanities, 2023)
This Service Learning Project Reflection in Afghanistan Relief Organization mainly focuses on my volunteer teaching during TESOL Graduate program at Kabul Education University. In this project, I discuss my understanding, experiences and my students’ beliefs about service learning. Service Learning Project Reflection in ARO is the community needs, especially the students who are orphanage students and I voluntarily be ready to teach them and share my experiences that I have learnt during my MA. Afghanistan Relief Organization is partnership of ACCESS, so when I start my service learning the students are happy and they engaged in the lesson, because it is necessary for them to understand what I am teaching to enrich their knowledge. Students who are in ARO studying full time and this service-learning course are optional. The purpose service learning, students learn more about their relationship with the communities they engage socially with classmates. Learn more about their capacity for serving others. Mostly in this course applied integrated speaking and reading English course involves forty hours teaching in ARO. Service-learning is an experiential learning pedagogy that moves students beyond the classroom to become active participants in their learning and develop community knowledge and skills. Objectives: The purpose of this article is to hold project service learning in ARO because of community needs and to develop students learning styles the process of learning through integrating reading and speaking skills.